Features of heating and melting of powder tape for surfacing of composite and complex-alloyed alloys - Kassov, Valeriy; Berezshna, Olena; Yermakova, Svitlana; Turchanin, Dmytro; Malyhina, Svetlana (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is a powder tape for arc surfacing of composite and complex-alloyed alloys. Essentially, the peculiarities of their design determine the uneven heating and melting of the shell and core during the arc surfacing process. This causes chemical heterogeneity of the surfacing metal, which leads to a spread of its mechanical properties. Taking into account the thermal balance of heating the powder tape protrusion by the welding current during surfacing, a mathematical model has been built. It allows for a reliable and operational assessment of thermal effects depending on the welding current density, geometric dimensions, the filler metal filling ratio of the tape and the thermophysical characteristics of the metal shell and ingredients. Its quantitative accuracy makes it possible to predict general patterns of temperature differences, changes in the aggregate state, heat and mass transfer, and phase transitions. It also allows for the calculation of the direction and limits of physicochemical reactions and the identification of ways to control the power parameters of the powder tape manufacturing process and the characteristics of the surfacing mode. Comparison of the calculated values of the average heating temperature with experimental data indicates the adequacy of the mathematical model and its feasibility for practical calculations. The data reported in the paper correctly reflect the nature of the heating of the powder tape, taking into account the composition of the core, the thickness of the shell, the size of the tape, the degree of compression of the metal shell and the powder core in the two-roll mill stand. Analytical description of the heating patterns makes it possible to solve under industrial conditions the technological tasks of improving the quality of the deposited metal, increasing the productivity of the process, as well as resource and energy saving when surfacing composite and alloyed wear-resistant alloys